Biliary sphincterotomy is not required for bile duct stent placement. Issue 1 (20th March 2013) - Wilcox, C. Mel; Kim, Hwasoon; Ramesh, Jayapal; Trevino, Jessica; Varadarajulu, Shyam
Abstract : Background: The aim of the present study was to assess the success and outcome of bile duct stent placement without the use of endoscopic biliary sphincterotomy (EBS). Patients and Methods: Over a period of 10 years and 9 months, all patients undergoing endoscopic retrograde cholangiopancreatography (ERCP) were prospectively identified. Bile duct stent placement was routinely done without EBS unless additional therapy (stone removal, multiple stenting) was anticipated. Results: Of 5020 patients who underwent ERCP, bile duct stents were placed in 1668 patients. After excluding those requiring additional endoscopic therapy, 1112 patients (89.5%) had ERCP and stent placement without a sphincterotomy and 130 patients (10.5%) had ERCP and stent placement with asphincterotomy. Deployed endoprostheses were self‐expandable metallic stents in 15.7% and plastic in 77.5%. Caliber of plastic stents was 10 Fr in 78.9% and <10 Fr in 21.1%. All stents were successfully placed in these 1112 patients without the need for EBS. Comparing patients undergoing bile duct stenting with and without sphincterotomy, no difference was seen in rates of pancreatitis (1.54% vs 2.07%, P  > 0.9999). Conclusion: Single bile duct stents, both plastic and metal, can be deployed without EBS.